Mutations in the RSK2(RPS6KA3) gene cause Coffin–Lowry syndrome and nonsyndromic X-linked mental retardation - Field, M (2006)
We describe three families with X-linked mental retardation, two with a deletion of a single amino acid and one with a missense mutation in the proximal domain of the RSK2(RPS6KA3) (ribosomal protein S6 kinase, 90 kDa, polypeptide 3) protein similar to mutations found in Coffin–Lowry syndrome (CLS). In two families, the clinical diagnosis had been nonsyndromic X-linked mental retardation. In the third family, although CLS had been suspected, the clinical features were atypical and the degree of intellectual disability much less than expected. These families show that strict reliance on classical clinical criteria for mutation testing may result in a missed diagnosis. A less targeted screening approach to mutation testing is advocated.